Determination of Some Quality Attributes of Feijoa Fruits [Acca sellowiana (Berg) Burret] at Different Ripening Stages - Silveira, Ana Cecilia; Oyarzún, Dennise; Záccari, Fernada; Rivas, Mercedes (Agrociencia Uruguay, 2020)
Feijoa [Acca sellowiana (Berg) Burret] is a native species whose fruits are appreciated for their content on compounds with antioxidant activity as polyphenols, flavonoids and vitamin C among others. In this study, 10 genetic materials derived from the Experimental Station of the School of Agriculture in Salto (EEFAS), Uruguay, were characterized. Husk thickness, flesh firmness, total polyphenols and antioxidant activity were determined on fruits harvested at three maturity stages (stage 1: immature fruits; stage 2: mature fruits; stage 3: overripe fruits). All measured variables decreased with the maturity progress. Selections 12, 14, 16 and 23, presented a thinner husk. The lowest loss of firmness was observed in the selections 17, 23 and 29 for both the fruits harvested in the mature state 1, and in state 2. The higher total polyphenols content corresponded to the selections 26 and 29, while the higher antioxidant activity was found on selections 14 and 26. The antioxidant activity and polyphenol content showed differences among maturity stages –where the highest values corresponded to the immature fruit–and among selections. Finally, genetic selections identified as 12, 14, 23 and 26 would be the most interesting ones because of their thinner husk, improved firmness, and higher content of phenolic compounds and antioxidant activity.